A New 3D Surface Reconstruction Method. (June 2020) - Fu, Wei; Wu, Lushen
Abstract: The existing complete orthogonal function system cannot introduce the spectrum analysis into geometry information processing field. This paper proposes complete orthogonal v system reconstruction method based on the 3D data mode, and this method is to map surface data model to parametric triangular domain. The complete orthogonal V system in triangular domain is used to expand the surface data model and the 3D model reconstruction with piecewise polynomial is realized, and it has simple operation and can handle any topology grid. The experimental results show that the error of three experimental models is controlled in 0.25 mm, Compared with Voronoi-based method and Yoshimoto's method, the accuracy of the proposed method is improved obviously, and the orthogonal v system under reconstruction time compared with Voronoi-based method reconstruction time is shortened by 13%. Therefore, reconstruction precision and speed can meet the requirements of industrial design.